PENINGKATAN KAPASITAS PRODUKSI IKAN MELALUI TEKNOLOGI ORGANIC WASTE TRAP DALAM SISTEM POLIKULTUR BAGI PEMBUDIDAYA IKAN DI DESA TUA TUNU, KOTA PANGKALPINANG - Eva Prasetiyono; Denny Syaputra; Robin Robin (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2015)
Fish farming activities carried out by fish farmers often face problems that cause production activities to be not optimal. In fact, increasing production capacity is very important to increase profits. Problems that often arise are basically common. However, due to a lack of mastery of technology and production management, these problems become a major obstacle to optimizing business activities. Fish farmers in Tua Tunu Village, Pangkalpinang City are fish farmers engaged in freshwater fish farming activities, especially catfish (Pangasius pangasius). So far, fish farming activities carried out by fish farmers have faced problems caused by two main factors, namely poor water quality in aquaculture ponds due to waste from feed and fish feces and lack of diversification of fish farming commodities. The purpose of this activity is to provide science and technology applications in the form of technology to minimize aquaculture waste and aquaculture technology systems so that the production capacity of fish farmers increases. This activity was carried out in fish farming ponds owned by fish farmers in Tua Tunu Village, Pangkalpinang City.The specific target is to increase the production capacity of fish farming with the application of technology in all fish farming ponds for fish farmers in Tua Tunu. The method used is a survey method by conducting fish farming activities by inserting technology applications in the form of organic waste trap technology and polyculture system technology. The results obtained show that the production capacity of the pond and the harvest of the fish farmers are more optimal. The results of the activity show that the fish farmer partners can harvest more types of fish and more profits. The water quality in the fish farming media is better. The good water quality from the application of this technology can be seen physically from the color of the water with a lower level of turbidity by suspended solids from feed compared to ponds that do not use this technology.